Hyperoxidation of Peroxiredoxins and Effects on Physiology of Drosophila - Austin McGinnis; Vladimir I. Klichko; William C. Orr; Svetlana N. Radyuk (MDPI AG, 2021)
The catalytic activity of peroxiredoxins (Prx) is determined by the conserved peroxidatic cysteine (CysP), which reacts with peroxides to form sulfenic acid (Cys-SOH). Under conditions of oxidative stress, CysP is oxidized to catalytically inactive sulfinic (Cys-SO2) and sulfonic (Cys-SO3) forms. The Cys-SO2 form can be reduced in a reaction catalyzed by sulfiredoxin (Srx). To explore the physiological significance of peroxiredoxin overoxidation, we investigated daily variations in the oxidation state of 2-Cys peroxiredoxins in flies of different ages, or under conditions when the pro-oxidative load is high. We found no statistically significant changes in the 2-Cys Prxs monomer:dimer ratio, which indirectly reflects changes in the Prx catalytic activity. However, we found daily variations in Prx-SO2/3 that were more pronounced in older flies as well as in flies lacking Srx. Unexpectedly, the srx mutant flies did not exhibit a diminished survivorship under normal or oxidative stress conditions. Moreover, the srx mutant was characterized by a higher physiological activity. In conclusion, catalytically inactive forms of Prx-SO2/3 serve not only as a marker of cellular oxidative burden, but may also play a role in an adaptive response, leading to a positive effect on the physiology of Drosophila melanogaster.